Exploring The Relationship Between Coping Self Efficacy and Dominance Prestige in Working Female - Shikha Yadav; Dr. Soni Kewalramani (International Journal of Indian Psychȯlogy, 2025)
The present study aimed to examine the relationship between self-efficacy and dominance prestige among 100 working females from diverse professional backgrounds. Self-efficacy was defined as the belief in one’s ability to execute tasks and handle challenges effectively, while dominance prestige referred to the perceived level of respect, influence, and authority within the workplace. A quantitative correlational research design was employed, and standardized psychological scales were used to measure both variables. The data were analyzed using Pearson’s correlation coefficient, which revealed a moderate, positive, and statistically significant correlation (r = 0.456, p = 0.002). These results indicated that participants who perceived themselves as having higher levels of dominance prestige also reported greater self-efficacy. The findings suggested that social recognition and perceived workplace status played a meaningful role in shaping women’s beliefs in their professional capabilities. The study concluded that fostering environments where women feel empowered and respected could contribute positively to their self-efficacy.